Comparative analysis of symmetric division deg index as potentially useful molecular descriptor. Issue 17 (20th May 2018) - Furtula, Boris; Ch. Das, Kinkar; Gutman, Ivan
Abstract: There are several dozens of vertex–degree–based (VDB) molecular structure descriptors currently studied and proposed to be used in quantitative structure‐property/activity relationships (QSPR/QSAR) researches. Among them, just a couple are recognized as promising and worth of practical applications. One of the newest is the symmetric division deg index ( SDD ). This article is devoted to a thorough multifaceted analysis of SDD and its comparison with other VDB topological indices. We show that the applicative potential of SDD is comparable to already well‐established VDB structure descriptors. Additionally, some of conducted tests indicate its supremacy over other VDB molecular indices. Abstract : Among several dozens of vertex‐degree‐based molecular descriptors, only few stand out for their applicability on real‐world systems. The recently proposed symmetric division deg index (SDD) is tested to evaluate its potential for applications. Results show that the prediction power of SDD index is comparable to that of the better‐known geometric‐arithmetic (GA) index. SDD results compare favorably against GA topological descriptors.